Peran Amerika Serikat dan Inggris terhadap Stabilitas Politik dan Keamanan Yordania dalam Perspektif Neorealisme - Azzura, Ghea; Lativa, Sovia; Jumhur, Muhamad Syahril (Journal of Integrative International Relations, 2023)
The United States (US) and UK have been Jordan's important partners since the country's early days until the present era. The formation of the Jordanian state was inseparable from the intervention of UK, which at that time won World War I. In the post-World War II era until the 2011 Arab Spring, the Middle East was a region that was always volatile and unstable. However, Jordan and its Hashemite Monarchy became one of the Arab countries that survived this turmoil and have survived to this day, 2022. The research focus of this article is to understand how the roles of the two Western powers can provide political stability and security for Jordan. The research method used is descriptive qualitative research method with data collection techniques through literature review. This study uses the theory of neorealism and the concept of bandwagoning which is its derivative as an analytical framework. The research result of this article is that Jordan applies the bandwagoning method by establishing very close political and security relations with the US and the UK. This relationship led to the US giving Jordan the status of a Major non-NATO Ally (MNNA). Jordan also chose bandwagoning against Israel which is a major US ally and previously a source of threat to the Arab nation. This has affected Jordan's political and security stability from internal and external threats until the present era.